Drogas psicoativas no ensino de química: uma abordagem CTS (Ciência, Tecnologia e Sociedade) para a EJA (Educação de Jovens e Adultos) - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Faced with the requirements in the teaching of chemistry for third year high school students of EJA, this project proposes to analyze the pertinence of the cross-sectional theme, psychoactive drugs, as the guiding axis for the teaching of chemistry in EJA, through the understanding of the concept of psychoactive drugs; the contents of organic chemistry that relate to the theme; of the Science, Technology and Society (CTS) approach that will increase students' criticality; and through the Harm Reduction (RD) strategy, so that students gain a broader awareness of the effects of psychoactive drugs on the human body and society. Several strategies will also be developed, such as: expository classes, group dynamics, setting of word-of-mouth, cross-montage assembly, experimental class and assembly of some organic structures.
Psychoactive drugs in chemistry teaching: a sts approach (science, technology and society) for eya (education of young people and adults)
Keywords: Drogas Psicoativas; Ensino de química; Abordagem CTS; EJA; Química; Psychoactive drugs; STS; Technology and society; Teaching chemistry; Harm reduction; Organic chemistry and STS; EYA; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA